Reproductive Health Problems and Treatment Seeking Behavior Among Adolescent Girls of UHTC Field Practice Area, Govt. Medical College, Bhavnagar - Mansi G Chauhan; Harshad Patel (National Journal of Community Medicine, 2016)
Background: Within the family, compared to boys, the ‘adolescent girls’ health, nutrition, education & development are more neglected and it has adverse effect on reproductive health. This study was conducted to assess awareness about reproductive health among adolescent girls & to study prevalence of reproductive health problems & treatment seeking behavior among adolescent girls for Reproductive Tract Infections (RTIs).